A Kontrol Diri dengan Motivasi Belajar SMA Negeri 1 - Shanam Al Dhuha; Octa Reni Setiawati; Sri Maria Puji Lestari; Prambudi Rukmono (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
the ability to guide their own behavior, the ability to suppress or inhibit impulses or impulsive behavior is a sense of self-control. a significant role in the effort to learn the definition of motivation. Because students are not possible without the motivation of learning activities. Learning is a complex process that happens to every person throughout his life. Between the self-control with student achievement there is a significant positive relationship. Thus, self-control is a control behavior that tends to act positively in thinking. Knowing the self-control relationship with the motivation to learn at SMA Negeri 1 Trimurjo Central Lampung. Research quantitative analytic design and cross-sectional design and sampling techniques Simple Random Sampling by questionnaire self-control and motivation to learn. Total sample 205 Of 500 population, self-control with a mean of 82.80 (medium), ± Std.Deviation (13 792), while the motivation to study with a mean of 80.94 (medium), ± Std.Deviation (13,572) for the motivation to learn. The results of the bivariate analysis values ​​obtained Pearson test P Value 0.003, and the value of r 0.209. There is a significant relationship between self-control and motivation to learn at Senior High School 1 Trimurjo Central District Lampung, with the strength and direction of the correlation was positive correlation that the higher the self control, the higher a person's motivation to learn.